Perinatal and maternal outcomes in planned home and obstetric unit births in women at 'higher risk' of complications: secondary analysis of the Birthplace national prospective cohort study. (21st January 2015) - Li, Y; Townend, J; Rowe, R; Brocklehurst, P; Knight, M; Linsell, L; Macfarlane, A; McCourt, C; Newburn, M; Marlow, N; Pasupathy, D; Redshaw, M; et al.
Abstract : Objective: To explore and compare perinatal and maternal outcomes in women at 'higher risk' of complications planning home versus obstetric unit (OU) birth. Design: Prospective cohort study. Setting: OUs and planned home births in England. Population: 8180 'higher risk' women in the Birthplace cohort. Methods: We used Poisson regression to calculate relative risks adjusted for maternal characteristics. Sensitivity analyses explored possible effects of differences in risk between groups and alternative outcome measures. Main outcome measures: Composite perinatal outcome measure encompassing 'intrapartum related mortality and morbidity' (intrapartum stillbirth, early neonatal death, neonatal encephalopathy, meconium aspiration syndrome, brachial plexus injury, fractured humerus or clavicle) and neonatal admission within 48 hours for more than 48 hours. Two composite maternal outcome measures capturing intrapartum interventions/adverse maternal outcomes and straightforward birth. Results: The risk of 'intrapartum related mortality and morbidity' or neonatal admission for more than 48 hours was lower in planned home births than planned OU births [adjusted relative risks (RR) 0.50, 95% CI 0.31–0.81]. Adjustment for clinical risk factors did not materially affect this finding. The direction of effect was reversed for the more restricted outcome measure 'intrapartum related mortality and morbidity' (RR adjusted for parity 1.92, 95% CI 0.97–3.80). Maternal interventions were lower in planned home births. Conclusions: The babies of 'higher risk' women who plan birth in an OU appear more likely to be admitted to neonatal care than those whose mothers plan birth at home, but it is unclear if this reflects a real difference in morbidity. Rates of intrapartum related morbidity and mortality did not differ statistically significantly between settings at the 5% level but a larger study would be required to rule out a clinically important difference between the groups.